Assessment of the mean glandular dose using LiF:Mg, Ti, LiF:Mg, Cu, P, Li2B4O7:Mn and Li2B4O7:Cu TL detectors in mammography radiation fields. (8th August 2016) - Fartaria, M J; Reis, C; Pereira, J; Pereira, M F; Cardoso, J V; Santos, L M; Oliveira, C; Holovey, V; Pascoal, A; Alves, J G
Abstract: The aim of this paper is the characterization of four thermoluminescence detectors (TLD), namely, LiF:Mg, Ti, LiF:Mg, Cu, P, Li2 B4 O7 :Mn and Li2 B4 O7 :Cu for the measurement of the entrance surface air kerma (ESAK) and estimation of the mean glandular dose (MGD) in digital mammography examinations at hospitals and clinics. Low-energy x-ray beams in the typical energy ranges of mammography, produced with a tungsten target and additional 60 µ m molybdenum filtration were implemented and characterized at the Laboratory of Metrology of Ionizing Radiation at Instituto Superior Técnico. These beams were used for the characterization of the TLDs in terms of sensitivity, linearity, reproducibility, energy dependence and fading at 40 °C. The energy dependence test was further extended using clinical beams produced by mammography units at hospitals and clinics. The method proposed by the International Atomic Energy Agency was used for the measurement of ESAK and assessment of MGD. The combined standard uncertainty for the measurement of ESAK (and MGD) was determined in accordance to the Guide to the expression of uncertainty in measurement. The x-ray beams generated in the 23–40 kVp range presented HVL values from 0.36 to 0.46 mm Al. The beam produced at 28 kVp (HVL 0.39 mm Al) was considered as reference. The radiation field defined a circle with 84 mm diameter with a maximum variation of the beam intensity of less than 1% at the top flat (plateau) within 4 cm of the central axis. The estimated total uncertainty for the measurement of air kerma was 0.42%. All the TL detectors tested showed good performance except the commercial Li2 B4 O7 :Mn (or TLD-800) which was excluded due to its poor sensitivity in our experimental set up. Both lithium fluorides showed better linearity and reproducibility as well as lower energy dependence and fading when compared to lithium borates. The stable behaviour of LiF:Mg, Ti and LiF:Mg, Cu, P detectors is reflected in the low combined standard uncertainty of ±5.6% and ±4.3% respectively (or ±5.1% and ±3.6% if fading is neglected). In general a total combined uncertainty lower than ±10% for the measurement of ESAK was obtained for the four TL materials studied.